A new species of Argeiopsis Kensley, 1974 (Crustacea: Isopoda: Bopyridae: Argeiinae) from the northern Arabian Sea - Boyko, Christopher B.; Kazmi, Quddusi B. (Zootaxa, 2005)
A parasitized specimen of Microprosthema validum Stimpson (Stenopodidea) from the Arabian Sea off Pakistan was found to bear a pair of bopyrid isopods referable to the genus Argeiopsis Kensley, 1974. Although damaged, these specimens clearly represent a new species that is only the second in the genus. This new species is described and illustrated and a discussion of previous records of the type species A. inhacae is given.